Pengaruh Kegiatan Pramuka terhadap Pembentukan Karakter Siswa di SMAS ST. Petrus Kewapante - Maria Florida Balik; Rudolfus Ali; Petrus Kpalet (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
The type of research used in this research is a descriptive research. In descriptive research the collected data is in the form of words or pictures so it does not press on numbers. The subject of this study is a scounting,principal,and a pkn subject teacher. Data collection techniques using observation,interviews,dokumentation. The results of this study show that the influence of scout activities on the formation of student’s characters in Smas ST. Petrus Kewapante is carried out through the role of scout builder as a guide to provide support and facilitate students with interesting activites and there are values in character education.the methods include the partice of the scout honor code on every activity in the open realm such as camp. The purpose of this study is to examine those found in scouting activities that can form student characters.